PENGARUH PERMAINAN ORIGAMI TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH 3-6 TAHUN DI KELURAHAN PERKAMIL LINGKUNGAN 8 KOTA MANADO - Julita Legi; Winarsi Molintao; Valensia Sumampouw (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Increasing fine motor development in preschool children is very important, because these skills influence various aspects of daily behavior. Children who have good fine motor skills can participate in play activities and interact with peers. This research aims to examine the influence of origami games on the fine motor development of children aged 3-6 years. This research uses a quantitative design with a Quasi experimental design, especially One-Group Pre-Post test Design. With the 16 children samples. The statistical test used is the "Wilcoxon" test with a confidence level of 95%. Before giving the origami game abnormal 8 respondents (50%), suspected 6 respondents (37.5%) normal 2 respondents (12.5%) and after giving the normal origami game 10 respondents (62.5%), suspected 4 respondents (25%) and abnormal 2 respondents (12.5%). The research results show the P value = 0.004 which means there is a significant influence of origami playing on fine motor development in preschool children at the research location. In conclusion, origami games have been proven to be effective in improving the fine motor development of preschool children. The suggestion from this research is that families who have children with fine motor skills can consider using origami games as a useful therapeutic method.